Anthology of Kokugaku Scholars : 1690-1898 - Bentley, John R. (Book collections on Project MUSE., 2017)
Kokugaku "national study" is an academic field of study that spans a number of disciplines, including philology, poetry, literature, linguistics, history, religion, and philosophy. It began as a movement to recapture a sense of Japanese uniqueness, by focusing on Japanese poetic and linguistic elements found in the earliest surviving texts. As the movement grew, there was an attempt to separate native religious elements from Buddhist elements. This expanded to a vigorous attempt to weed out Confucian (and by extension anything "Chinese") elements from native elements. This began as an investigation into the earliest anthology, Man'yoshu, which some Kokugaku scholars argued preserved a pristine picture of the "true heart" of the ancients. Kokugaku matured under the tutelage of Kamo no Mabuchi and Motoori Norinaga, and expanded to include literary, linguistic, and historical analysis. With the death of Norinaga the philosophy of the movement fractured, and under Hirata native religious elements were amplified, with an advance toward nationalism. This anthology contains 26 essays by 13 influential Kokugaku scholars, covering roughly two centuries of thought, from 1690 down to the beginning of the Meiji Restoration in 1868. The volume is arranged according to four subjects: poetry, literature, scholarship, and religion/Japan (as a state).